PENERAPAN TEKNOLOGI AKUSTIK PADA PERIKANAN BAGAN PERAHU - Muhammad Kurnia; Sudirman Sudirman; Alfa Nelwan (Jurnal Perikanan Universitas Gadjah Mada, 2016)
Acoustic technology for fisheries is one of technologies with the advantages to detect marine resources including estimating density and the presence of fish and relatively more accurate than conventional methods. The present study aims to assess the effectiveness of the operation of the lift-net with hydroacoustic technology in an effort to increase the productivity of the fisherman of boat liftnet. The study was conducted on fishing activity of boat liftnet in the Makassar Strait from April to May 2015 by utilizing the tools of acoustic technology in the operation of the boat liftnet. The analysis method is based on the productivity of the boat liftnet. The results showed that the productivity of fishing gear which is operated by using the tools of fisheries acoustic were improved compared with the fishing effort without acoustic tools. This result is expected to be a reference to research on the use of acoustic technology in a variety of fishing gear and as reference to research the use of science and technology in support of sustainable small-scale fishing effort.